2021
DOI: 10.1007/s00170-021-07495-4
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of direct energy deposition via structured light system and its application in remanufacturing industry

Abstract: The Direct Energy Deposition (DED) process utilizes laser energy to melt metal powders and deposit them on the substrate layer to manufacture complex metal parts. This study was applied as a remanufacturing and repair process to fix used parts, which reduced unnecessary waste in the manufacturing industry. However, there could be defects generated during the repair, such as porosity or bumpy morphological defects. Traditionally the operator would use a design of experiment (DOE) or simulation method to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Structured light, on the other hand, provides detailed 3D models but requires controlled lighting and can be time-consuming and difficult to utilize for complex parts [147]. Though laser triangulation and structured light may be favourable in regard to the measurement of surface roughness, object size, and measurement accuracy, they struggle with highly reflective or absorptive surfaces, such as those found in finished metal AM [141,176,[206][207][208][209][210][211][212]. On the other hand, interferometry delivers high precision over small areas but is highly sensitive to vibrations and environmental changes [184].…”
Section: Laser-based Scanningmentioning
confidence: 99%
“…Structured light, on the other hand, provides detailed 3D models but requires controlled lighting and can be time-consuming and difficult to utilize for complex parts [147]. Though laser triangulation and structured light may be favourable in regard to the measurement of surface roughness, object size, and measurement accuracy, they struggle with highly reflective or absorptive surfaces, such as those found in finished metal AM [141,176,[206][207][208][209][210][211][212]. On the other hand, interferometry delivers high precision over small areas but is highly sensitive to vibrations and environmental changes [184].…”
Section: Laser-based Scanningmentioning
confidence: 99%
“…Researchers have already attempted to employ fringe projection for in-situ monitoring of additive manufacturing processes such as laser powder bed fusion (LPBF) [41,42,43,44] or direct energy deposition (DED) [45]. An example of using fringe projection for in-situ/in-process monitoring of a DED process by the author's research group [45] is shown in Fig. 3.…”
Section: In-situ/in-process Monitoringmentioning
confidence: 99%
“…19 For AM parts, CT scanning has proven to be very useful in understanding the benefits, and consequences, of using AM for repairs. 20 Stress intensity factor (SIF) values are representative of the significance of the stress in each location, and it accounts for the consequences of having pores in these locations as well. 21 Similar concepts implementing SIF calculations have been proposed in fatigue life prediction approaches that examine the effects of pores on the fatigue life of an AM part.…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing the pores in an AM part, before testing procedures occur, gives insight to information that would otherwise be completely unknown until the testing was concluded 19 . For AM parts, CT scanning has proven to be very useful in understanding the benefits, and consequences, of using AM for repairs 20 …”
Section: Introductionmentioning
confidence: 99%